2021
DOI: 10.3390/biom11121775
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches in Lysosomal Storage Diseases

Abstract: Lysosomal Storage Diseases are multisystemic disorders determined by genetic variants, which affect the proteins involved in lysosomal function and cellular metabolism. Different therapeutic approaches, which are based on the physiologic mechanisms that regulate lysosomal function, have been proposed for these diseases. Currently, enzyme replacement therapy, gene therapy, or small molecules have been approved or are under clinical development to treat lysosomal storage disorders. The present article reviews th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Prior to the introduction of ERT, treatment was essentially palliative and aimed to relieve symptoms. ERT studies in animal models of Fabry disease and other LSDs showed that intravenously infused lysosomal enzymes are rapidly taken up by the liver, spleen and other peripheral tissues, but do not normally reach the brain parenchyma [ 109 ]. Some of the problems associated with the use of ERT are the reduced efficacy of therapy at the CNS level, the immune response to the replacement protein, the use of lifelong therapy and the high cost of treatment [ 48 , 76 ].…”
Section: Therapies For Fdmentioning
confidence: 99%
“…Prior to the introduction of ERT, treatment was essentially palliative and aimed to relieve symptoms. ERT studies in animal models of Fabry disease and other LSDs showed that intravenously infused lysosomal enzymes are rapidly taken up by the liver, spleen and other peripheral tissues, but do not normally reach the brain parenchyma [ 109 ]. Some of the problems associated with the use of ERT are the reduced efficacy of therapy at the CNS level, the immune response to the replacement protein, the use of lifelong therapy and the high cost of treatment [ 48 , 76 ].…”
Section: Therapies For Fdmentioning
confidence: 99%
“…Several approaches for the treatment of Fabry disease have been exploited, both preclinically and clinically, including enzyme replacement therapy (ERT), gene therapy, and chaperone therapy ( Solomon and Muro, 2017 ; Castelli et al, 2021 ; Fernández-Pereira et al, 2021 ). Despite the success of these therapeutic strategies, each approach has its limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Among those disorders are countless rare diseases of monogenic origin, including the lysosomal storage diseases (LSDs) that were our major focus of interest. LSDs are a particular subset of genetic diseases that can benefit greatly from even the slightest increase in protein function [ 5 ]. The vast majority of LSDs are autosomal recessive, even though three X-linked diseases are also known.…”
Section: Introductionmentioning
confidence: 99%